Motivation Influenced by Seating Arrangement in an ESL Classroom (2019)
This research was an attempt to determine the influence that seating arrangement has in an English as second language classroom in order to improve integrated skills. While it is clear students present lack of interest in learning English, it is necessary to evaluate the different aspects that cause this disinterest, furthermore Multiple factors that affect the classroom environment can be identified and affect the concentration, motivation, participation and interaction of the students. According to the above, there is a need to look for strategies that allow the free development and expression of the students so that they can achieve an active way of learning. This paper aims to highlight the advantages and disadvantages of having a more didactic organization of the sitting arrangement compared to the traditional one in the English learning classes. Knowing that nowadays teachers do not focus on seating arrangement, this paper shows some easy strategies that can be used in regular classes, especially on second grade students. Due to time issues the methodology selected for this research could not be implemented.